Pengaruh Penempatan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening Pada PT Yamaha Musical Products Indonesia - E P, M Habibur Rohman; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine and analyze the influence of work placement and work discipline on employee performance with motivation as an intervening variable at PT Yamaha Musical Products Indonesia. The population in this study were production employees in the surface treatment section at PT. Yamaha musical products Indonesia (YMPI). The data collection method in this research used a questionnaire with a sample size determined using the Slovin formula and the results obtained were 84 respondents. Data testing techniques used in this research include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t test, coefficient of determination test (R²) and Path Analysis test (Path Test). The research results show that work placement and work discipline influence work motivation. Work placement, work discipline and motivation influence employee performance. Work placement and work discipline influence employee performance through work motivation  Keywords: Job Placement, Work Dicipline, Employee Motivatiion, Employee Performance.